USULAN PERBAIKAN SISTEM KERJA PADA DEPARTEMEN CNC DI PT OPTIMECH ENGINEERING PRODUCT AND SERVICES - Tampubolon, Roni Chandra; Tarigan, Elsya Paskaria Loyda (LPPM Universitas Putera Batam, 2023)
Competition between companies in the manufacture of increasingly strict industrial products, pt optimech engineering is still facing obstacles such as production time that does not meet the target.This restriction occurs due to the frequent occurrence of products that do not conform to the specifications because the equipment used for production has a low capacity and does not correspond to the quantity of production performed.The purpose of this research is to identify and provide proposals for repair of the work system so that it can eliminate waste found in the cnc department and know the changes that occur in the proposal for repair of the production process.Based on the waste assessment model (WAM), The defect is a percentage of 24.01%, and the waste defect also significantly affects the occurrence of other waste.From the results of the fishbone diagram summarized a number of possibilities which are considered to be the root of the problem, It is a basis for repair recommendations. Work system improvements can be done by accurately predicting and planning production in order to avoid overinventory and could harm the company, supplying employees with more insight into the work and handling of products, and do control for materials before being sent to the next process do the supply of machines according to the production capacity and complexity of products and machine repairs periodically, use or do machine purchases according to the body dimension the labor is owned and does things that can motivate employees to be able to work well.